¿Qué es transparencia? - Ramírez Villaescusa, Rafael (UNIVERSIDAD DE SONORA, 2019)
he recent democratic development process in Mexico has been accompanied of several policies to enhance civic participation and to strength government accountability. One of those actions was the enactment of the Federal Law of Governmental Transparency and Access of Information, during president Fox administration. Those actions took part in acontext of international promotion of right to know acts and policies. It's seems that transparency just arrived to stay for a long time, but that doesn't mean that our democratic consolidation has reach an end. The present essay is part of a set of articles that seek to promote an interdisciplinary approach to transparency. Particularly, the present article corresponds to a descriptive analysis of transparency from a legal perspective